Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the equation [tex]\(\sin(3x + 13^\circ) = \cos(4x)\)[/tex], we need to find an [tex]\(x\)[/tex] that satisfies this trigonometric identity.
First, recall the co-function identity: [tex]\(\cos(\theta) = \sin(90^\circ - \theta)\)[/tex]. Using this, we can rewrite [tex]\(\cos(4x)\)[/tex] in terms of sine:
[tex]\[ \cos(4x) = \sin\left(90^\circ - 4x\right) \][/tex]
Thus, the given equation transforms to:
[tex]\[ \sin(3x + 13^\circ) = \sin(90^\circ - 4x) \][/tex]
For this equality to hold, the arguments of the sine functions must either be equal or differ by multiples of [tex]\(180^\circ\)[/tex], due to the periodicity and symmetry of the sine function. Thus, we have two cases to consider:
Case 1:
[tex]\[ 3x + 13^\circ = 90^\circ - 4x + 360^\circ k \quad \text{for any integer } k \][/tex]
Simplifying,
[tex]\[ 3x + 4x = 90^\circ - 13^\circ + 360^\circ k \][/tex]
[tex]\[ 7x = 77^\circ + 360^\circ k \][/tex]
[tex]\[ x = 11^\circ + 51.43^\circ k \][/tex]
By considering integer values for [tex]\(k\)[/tex], we find that [tex]\(x = 11^\circ\)[/tex] is a possible solution.
Case 2:
[tex]\[ 3x + 13^\circ = 180^\circ - (90^\circ - 4x) + 360^\circ k \][/tex]
[tex]\[ 3x + 13^\circ = 90^\circ + 4x + 360^\circ k \][/tex]
Simplifying,
[tex]\[ 3x - 4x = 90^\circ - 13^\circ + 360^\circ k \][/tex]
[tex]\[ -x = 77^\circ + 360^\circ k \][/tex]
[tex]\[ x = -77^\circ - 360^\circ k \][/tex]
This scenario does not yield an [tex]\(x\)[/tex] within the provided answer choices as valid solutions.
Given the solutions derived from comprehensive analysis, [tex]\(x = 11^\circ\)[/tex] matches with the given answer choices.
Thus, the correct answer is:
[tex]\[ \boxed{11^\circ} \][/tex]
First, recall the co-function identity: [tex]\(\cos(\theta) = \sin(90^\circ - \theta)\)[/tex]. Using this, we can rewrite [tex]\(\cos(4x)\)[/tex] in terms of sine:
[tex]\[ \cos(4x) = \sin\left(90^\circ - 4x\right) \][/tex]
Thus, the given equation transforms to:
[tex]\[ \sin(3x + 13^\circ) = \sin(90^\circ - 4x) \][/tex]
For this equality to hold, the arguments of the sine functions must either be equal or differ by multiples of [tex]\(180^\circ\)[/tex], due to the periodicity and symmetry of the sine function. Thus, we have two cases to consider:
Case 1:
[tex]\[ 3x + 13^\circ = 90^\circ - 4x + 360^\circ k \quad \text{for any integer } k \][/tex]
Simplifying,
[tex]\[ 3x + 4x = 90^\circ - 13^\circ + 360^\circ k \][/tex]
[tex]\[ 7x = 77^\circ + 360^\circ k \][/tex]
[tex]\[ x = 11^\circ + 51.43^\circ k \][/tex]
By considering integer values for [tex]\(k\)[/tex], we find that [tex]\(x = 11^\circ\)[/tex] is a possible solution.
Case 2:
[tex]\[ 3x + 13^\circ = 180^\circ - (90^\circ - 4x) + 360^\circ k \][/tex]
[tex]\[ 3x + 13^\circ = 90^\circ + 4x + 360^\circ k \][/tex]
Simplifying,
[tex]\[ 3x - 4x = 90^\circ - 13^\circ + 360^\circ k \][/tex]
[tex]\[ -x = 77^\circ + 360^\circ k \][/tex]
[tex]\[ x = -77^\circ - 360^\circ k \][/tex]
This scenario does not yield an [tex]\(x\)[/tex] within the provided answer choices as valid solutions.
Given the solutions derived from comprehensive analysis, [tex]\(x = 11^\circ\)[/tex] matches with the given answer choices.
Thus, the correct answer is:
[tex]\[ \boxed{11^\circ} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.